LearnLink: Artificial Intelligence-Based E-Learning Companion for High School Students - Raja Kumar, Dharvina; Hafit, Hanayanti (Applied Information Technology And Computer Science, 2025)
LearnLink, an innovative e-learning platform tailored for ICT club students at SMK Puchong Batu 14, integrates artificial intelligence (AI) to revolutionize high school coding education. Overcoming challenges in traditional methods, LearnLink targets issues like engagement, personalization, real-time assessment, and resource scarcity. Using technologies like Visual Studio and ChatGPT API, the platform aims to deliver a user-friendly, comprehensive e-learning experience. By addressing these challenges head-on, LearnLink seeks to empower students with vital coding and programming skills, fostering engagement and personalization to bridge existing gaps in digital education. For this project, the prototype model is used to develop it since the desired system needs a lot of interaction with end users.